Fault Diagnosis of the Three-phase Asynchronous Motor Bond Graph Model Based on Bond Graph and Temporal Causal Graph. Issue 1 (1st February 2023) - He, Feng; Wang, Junnian; Yu, Wenxin; Zhong, Guangan
Abstract: The bond graph and temporal causal graph (TCG) are proposed to diagnose the fault of three-phase asynchronous motors. The bond graph model of the three-phase asynchronous motor is constructed using the general equations in the three-phase coordinate system. The analytical redundancy relationships (ARRs) and fault signature matrix (FSM) of the three-phase asynchronous motor are derived systematically by introducing TCG to improve the system fault isolability. Simulation experiments are conducted for the rotor-turn short-circuit fault and the rotor-break bar fault of the three-phase asynchronous motor. The experimental results show that introducing TCG for fault diagnosis in this model is feasible.